ICC 2021 - IEEE International Conference on Communications 2021
DOI: 10.1109/icc42927.2021.9500392
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Local Local Oscillator for the Satellite-to-Earth Channel

Abstract: Continuous variable quantum key distribution (CV-QKD) offers information-theoretic secure key sharing between two parties. The sharing of a phase reference frame is an essential requirement for coherent detection in CV-QKD. Due to the potential attacks related to transmitting the local oscillator (LO) alongside quantum signals, there has been a focus on using local LOs (LLOs) to establish a shared phase reference. In this work, we develop a new noise model of a current state-of-theart LLO scheme in the context… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…CV-QKD exploits the heritage of classical optical communication in terms of highspeed components and space qualification and may bring a breakthrough in this field. Currently, the progress in satellite CV-QKD mainly focuses on the investigation of feasibility theoretically considering the fluctuation effects in realistic satellite-to-ground links and calculating the secret key rate of Gaussian modulation CV-QKD (Kish et al, 2020;Villasenor et al, 2020;Dequal et al, 2021). The preliminary experimental study was implemented in terms of signal measurement in satellite-to-ground links (Günthner et al, 2017).…”
Section: Neural Network Methodsmentioning
confidence: 99%
“…CV-QKD exploits the heritage of classical optical communication in terms of highspeed components and space qualification and may bring a breakthrough in this field. Currently, the progress in satellite CV-QKD mainly focuses on the investigation of feasibility theoretically considering the fluctuation effects in realistic satellite-to-ground links and calculating the secret key rate of Gaussian modulation CV-QKD (Kish et al, 2020;Villasenor et al, 2020;Dequal et al, 2021). The preliminary experimental study was implemented in terms of signal measurement in satellite-to-ground links (Günthner et al, 2017).…”
Section: Neural Network Methodsmentioning
confidence: 99%
“…The orange lines between point A and the first satellite on the left, as well as between satellites, and between the last satellite on the right and point B represent the classic channels, which are required in all teleportation protocols to finish characterizing the teleported state at the destination, since this example uses the quantum repeaters technique of the forward cascade type. In addition, in a quantum key distri-bution (QKD) context, [33][34][35][36][37][38][39][40][41] entanglement swapping type quantum repeaters expose the key as it passes through the same quantum repeater, which is why the technology selected for this experiment is the best, not only for communication performance, but also from a security point of view. Regarding quantum channels (yellow), the pairs of distributed entangled photons are of the |𝛽 00 ⟩-type, while the classical channels (orange) correspond to radio transmissions of the electromagnetic type in X or S Bands.…”
Section: An Example Of Multi-orbit Architecturementioning
confidence: 99%
“…[12] In these works, [6][7][8][9][10] it is also shown that all the quantum communications protocols [13] to be used in the future Quantum Internet [14][15][16][17][18][19][20][21][22][23][24] have the QFT as structural support. In this sense, we can mention the quantum teleportation protocol, [25][26][27][28][29][30] as well as all the protocols involved in quantum cryptography, [31] among which: quantum secret sharing (QSS), [32] quantum key distribution (QKD) [33][34][35][36][37][38][39][40][41] (with and without entangled photons, which require quantum repeaters [42,43] in both their terrestrial and space implementations to extend their range), and quantum secure direct communications (QSDC) [44,45] (which currently can operate with or without entangled photons and does not require the use of keys to encrypt the message to be transmitted) stand out. However, we must also take into account the presence of QFT in all quantum gates [6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to the use of real local oscillators (RLOs), also known as local local oscillators, which are phase-corrected using reference pulse information multiplexed with the signals. This latter approach using RLOs can be considered state-of-the-art for CV-QKD [57,58]. We have not attempted to provide a complete methodology of CV-QKD here.…”
Section: Figurementioning
confidence: 99%